Evaporation of binary droplets on heated superamphiphobic surfaces; International Journal of Heat and Mass Transfer; Vol. 240 - Youquan Jia; Yi Xu; Jun Zhang; Wenbin Niu; Jiadong Zang; Wenlong Lu; Piskunov M. V. Maksim Vladimirovich; Ran Tao; Longquan Chen (2025, 2025)
Title screen